Differentiating the levels of risk for muscle dysmorphia among Hungarian male weightlifters: A factor mixture modeling approach. (January 2015) - Babusa, Bernadett; Czeglédi, Edit; Túry, Ferenc; Mayville, Stephen B.; Urbán, Róbert
Highlights: We aimed to distinguish the levels of risk for muscle dysmorphia among weightlifters. Factor mixture modeling differentiated three independent groups of male weightlifters. The estimated prevalence of high risk muscle dysmorphia was 15.1%. A cut-off score for the Muscle Appearance Satisfaction Scale has been proposed for the identification of high risk muscle dysmorphia. Abstract: Muscle dysmorphia (MD) is a body image disturbance characterized by a pathological preoccupation with muscularity. The study aimed to differentiate the levels of risk for MD among weightlifters and to define a tentative cut-off score for the Muscle Appearance Satisfaction Scale (MASS) for the identification of high risk MD cases. Hungarian male weightlifters ( n = 304) completed the MASS, the Exercise Addiction Inventory, and specific exercise and body image related questions. For the differentiation of MD, factor mixture modeling was performed, resulting in three independent groups: low-, moderate-, and high risk MD groups. The estimated prevalence of high risk MD in this sample of weightlifters was 15.1%. To determine a cut-off score for the MASS, sensitivity and specificity analyses were performed and a cut-off point of 63 was suggested. The proposed cut-off score for the MASS can be useful for the early detection of high risk MD.